Global, regional, and national pancreatitis burden and health inequality of pancreatitis from 1990 to 2019 with a prediction from 2020 to 2034 - Yu Wen; Yuan Luo; Yunpeng Huang; Zijian Zhang; Li Xiong; Yongxiang Wang (BMC, 2024)
Abstract Background Pancreatitis is a digestive system disease that imposes a significant burden on society. However, there is a lack of comprehensive research on the incidence, prevalence, mortality, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) of pancreatitis, as well as on health inequalities and future trends. Methods Pancreatitis burden data, including the number and age-standardized rates (ASR) of incidence, prevalence, deaths, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs), were collected from the Global Burden of Diseases 2019 (GBD 2019). SDI and HDI were used to analyze the influence of societal development on the burden of pancreatitis in the population. Additionally, the Gini coefficient and the Concentration index were used to assess health inequalities in the burden of pancreatitis. Global population data from 1990 to 2034 was obtained from WHO. Based on the population data and pancreatitis burden data, a prediction model of the burden was constructed to calculate the number and ASR of incidence, prevalence, deaths, YLLs, YLDs, and DALYs from 2019 to 2034 using the BAPC package and the Nordpred package. Results From 1990 to 2019, there has been a decreasing trend in the ASR of incidence, prevalence, deaths, YLLs, YLDs, and DALYs in pancreatitis. However, despite this decline, the number of cases has been on the rise. Furthermore, pancreatitis imposes a higher burden on males in comparison to females, and there exists a negative correlation between pancreatitis burden and both the Social Development Index (SDI) and the Human Development Index (HDI). Additionally, health inequalities have progressively worsened globally between 1990 and 2019, particularly concerning the burden of pancreatitis in countries with low Social Development Index (SDI). Looking to the future, it is projected that the number of deaths and new cases will continue to increase from 2020 to 2034. Conclusions Pancreatitis remains a mounting worldwide burden. In order to alleviate this challenge, preventive strategies should focus on males and middle-aged or older individuals, specifically in countries with a low SDI. Pancreatitis is expected to predominantly impact Eastern Europe, characterized by a high ASR of incidence, and Asia, boasting a substantial population.